2021
DOI: 10.47750/cibg.2021.27.02.202
|View full text |Cite
|
Sign up to set email alerts
|

Examine The Influence Of Green Human Resource Management On Environmental Performance: Mediating Role Of Organizational Focused Citizenship Behaviour Towards The Environment

Abstract: The awareness about environmental concerns in organizations has been increased in recent research. Green human resources are becoming a crucial element to implement green practices in organizations. Limited research in the context of the inefficient environmental performance of universities is drawing the attention of scholars. Based on the Ability -Motivation-Opportunity (AMO) theory, the current study examines the indirect effect of GHRM practices on universities' environmental performance through organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…The results of the hypothesis testing revealed that GHRM practices, including Green Recruitment and selection, Green Training and Development, Green Performance Appraisal, and Green Compensation Management, were significantly correlated with the firm’s environmental performance. These findings align with previous investigation that highlights the positive impact of GHRM practices on the environment’s performance [ 16 , 33 ].…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the hypothesis testing revealed that GHRM practices, including Green Recruitment and selection, Green Training and Development, Green Performance Appraisal, and Green Compensation Management, were significantly correlated with the firm’s environmental performance. These findings align with previous investigation that highlights the positive impact of GHRM practices on the environment’s performance [ 16 , 33 ].…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The results of the hypothesis testing revealed that GHRM practices, including Green Recruitment and selection, Green Training and Development, Green Performance Appraisal, and Green Compensation Management, were significantly correlated with the firm's environmental performance. These findings align with previous investigation that highlights the positive impact of GHRM practices on the environment's performance [16,33]. The significant connections between these GHRM practices and the performance of the environment suggest that organizations can enhance their environmental performance by implementing green practices in various HRM areas.…”
Section: Discussion Of Resultssupporting
confidence: 90%
See 1 more Smart Citation